Analysis of Caffeine Content of Robusta Coffee Powder from the Coffee Powder Industry in Pasaman Regency - Rahmatika; Azrifirwan; Gunarif Taib (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Determining the level of caffeine in coffee grounds is very important so that people can consume coffee in a safe amount. Based on SNI 01-7152-2006 the permitted dose of caffeine is 50-150 mg/day. This study aims to describe the level of caffeine in local coffee powder originating from coffee powder SMEs in Pasaman Regency. Coffee powder samples were taken from the two largest coffee powder SMEs in Pasaman Regency, namely Matahari coffee powder SMEs and Gunpas coffee powder SMEs. The caffeine content obtained in this study will be compared with the standard caffeine content according to SNI 013542-2004 which is 0.45-2.00% and SNI 01-7152-2006 which is the maximum limit for caffeine consumption per day of 50-150 mg/day. The method used in this research is UV-Vis spectrophotometry. The results of the analysis of caffeine levels in four samples per 1 gram of coffee powder are sample A 6.878 mg; sample B 6.855mg; sample C 6,674mg; sample D 7,688mg. In one cup of coffee, 4 grams of coffee powder is used, so that the caffeine content of coffee powder circulating in Pasaman Regency is still safe for consumption per day. In percentage units of caffeine content, based on the four samples analyzed, sample A is 0.687%; sample B 0.685%; sample C 0.667%; sample D 0.768%. The coffee caffeine content produced is following with the requirements of SNI 01-3542-2004.